New species and records of Omaliini from East Asia (Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2017)
Rove beetles of the tribe Omaliini MacLeay, 1825 (Staphylinidae: Omaliinae) are quite diverse both in terms of morphology and biotopic preferences, they are widespread in all zoogeographic regions of the World (Herman 2001), however they still remain extremely fragmentally studied, and the fauna of the eastern Palearctic is not an exception.